تعالقات السياسة والأخلاق بتحولات الهوية الغربية: فخر المثلية نموذجأ: (The Interplay of Politics and Ethics in the Transformations of Western Identity - LGBT Pride as a Model) - Alrefai, Ayman; Murshed, Amer Abdulwahab; Syed Ismail, Sharifah Hayaati (Online Journal of Research in Islamic Studies, 2023)
This study addresses the problem of identity and the centrality of values and ethics in Western culture and its relationship with politics, which has influenced its historical transformations. The aim of this study is to uncover the pivotal role that politics has played and continues to play throughout history in shifting the centrality of values in Western society, particularly in Europe. Consequently, it examines its capacity to control Western identity and culture willingly according to the desires and ideological orientations of its political system. The research questions this study attempts to answer is: How did politics, assumed to be an outcome of society and culture, manage to become the main player in reshaping the culture and identity of Western society? And why were values and ethics the most important tools in executing this transformation? To answer this question, the study employs a historical approach to investigate the role of politics in the West throughout its long history. It focuses on some contemporary key phenomena that have resulted from this role and their impact on Western identity and culture. These phenomena include anti-Semitism, Islamophobia, xenophobia, and LGBTQ pride. Through this analysis, the study concludes that the Western society's abandonment of its primary role in preserving its moral values and ethics, which constitute its identity and culture, in favor of politics and corrupt politicians and economists, has led to the destruction of the Enlightenment heritage that once elevated the West to its highest civilization. This role will ultimately lead Western society to an inevitable abyss, subject to the laws of civilization and the philosophy of history. This study falls within the methodological field of critical analytical studies. Its core lies in discussing and analyzing the problematic aspects of Western culture, elucidating the historical role of politics in its formation, and revealing the duality of contemporary European moral values and their immense impacts within the comprehensive interactive context.